The empress in the Pepper Chamber : Zhao Feiyan in history and fiction - Milburn, Olivia (University of Washington Press, 2021)
"Zhao Feiyan (45-1 BCE), the second empress appointed by Emperor Cheng of the Han dynasty (207 BCE-220 CE), was born in slavery and trained in the performing arts, a background that made her appointment as empress highly controversial. Subsequent persecution by her political enemies eventually led to her being forced to commit suicide. After her death, her reputation was marred by accusations of vicious scheming, murder of other consorts and their offspring, and relentless promiscuity, punctuated by bouts of extravagant shopping. This first book-length study of Zhao Feiyan and her literary legacy includes a complete translation of The Scandalous Tale of Zhao Feiyan (Zhao Feiyan waizhuan), a Tang dynasty (618-907 CE) erotic novella that describes in great detail the decadent lifestyle enjoyed by imperial favorites in the harem of Emperor Cheng. This landmark text was crucial for establishing writings about palace women as the accepted forum for discussing sexual matters, including fetishism, obsession, jealousy, incompatibility in marriage, and so on. Using historical documentation, Olivia Milburn reconstructs the evolution of Zhao Feiyan's story and illuminates the broader context of palace life for women and the novella's social influence"-- Provided by publisher.
Keywords: Ling, Xuan. -- Zhao Feiyan wai zhuan.; Zhao, Feiyan, -- 34 B.C.-1 B.C. -- In literature.; Zhao, Feiyan, -- 34 B.C.-1 B.C.; Empresses -- China -- Biography -- History and criticism.; Impératrices -- Chine -- Biographies -- Histoire et critique.; HISTORY / Asia / China; Empresses -- Biography; Literature; China; Criticism, interpretation, etc.